2015
DOI: 10.3329/ptcb.v24i2.23559
|View full text |Cite
|
Sign up to set email alerts
|

Rapid in vitro shoot regeneration of Valeriana officinalis

Abstract: A protocol for efficient and rapid regeneration of medicinal plant (Valeriana officinalis L.) was developed by in vitro culture of crown division. The effect of three different culture media, MS, B5 and MB (a new combined medium) containing 12 combinations of BAP and NAA was evaluated on regeneration and growth parameters. Results revealed a significant response of media used for shoot regeneration. The best frequency of regenerated plantlets (80%) and number of regenerated shoots (9.43) were obtained on MB co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The obtained results clearly showed that the high percentage of acclimatized and survival plantlets 73.67±5.55 a was recorded with culturing of in vitro derived plantlets in nutrient media containing peat-moss and vermiculite at 1:1 as shown Fig. (13,14). However, the minimum number of acclimatized and survival plantlets 36.33±3.48 b were recorded with culturing of in vitro derived plantlets on sand media.…”
Section: Hardening and Acclimatizationmentioning
confidence: 86%
See 2 more Smart Citations
“…The obtained results clearly showed that the high percentage of acclimatized and survival plantlets 73.67±5.55 a was recorded with culturing of in vitro derived plantlets in nutrient media containing peat-moss and vermiculite at 1:1 as shown Fig. (13,14). However, the minimum number of acclimatized and survival plantlets 36.33±3.48 b were recorded with culturing of in vitro derived plantlets on sand media.…”
Section: Hardening and Acclimatizationmentioning
confidence: 86%
“…The obtained regenerated shoots derived from callus of leaf explant have shown that the best-regenerated media affected on a percentage of regenerated shootlets, length of shoot, several shoots, number of the leaf, and length of plantlets were MS+3ppm BA+1ppm 2,4-D (33±4.04 a ,14.67±0.77 a , 1.67±0.33 a , 2.67±0.33 a , 20.67±1.76 a ). Whereas Tansaz et al, 2014 [14]reported that BA (0.5 mg/l) +NAA (0.25mg/lon MB(half (MS+B5) salts and vitamins, 10 ml/l Fe EDTA (iron stock) + 2.5% sucrose) achieved of shoot length using MB with BA (1 mg/l) + (0.5 mg/l). Adversely to Ghaderi & Jafari 2014 [11]who have shown that media supplemented with Thidiazuron(TZD) and NAA have marked regeneration yield from petiole and leaf explants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation